Double cordon tolls in urban areas to increase social welfare - Santos, G (Transportation Research Board of the National Academies, 2002)
A second-best traffic demand management policy, cordon tolls, is considered. Double cordons are simulated for seven English towns. It is found that a second, outer cordon implemented jointly with an inner cordon surrounding the city center enhances the increase in social welfare in comparison with a single inner cordon. Although other social and political considerations such as potential revenues and distributional effects may persuade policy makers to implement higher or lower charges, a method is proposed for deciding on the optimal combination of tolls, which is defined as the combination that maximizes the increase in social welfare for a given cordon location, social welfare being equal to the sum of individual utilities minus the sum of individual costs.